A Quantitative Analysis of Harmonic Effects on the Accuracy of Single-Phase kWh Meters in PT. PLN (Persero) ULP Kuta - Sutama, I Wayan; Falah, Muhammad Yusrul; Putri, Dewa Ayu Putu Adhiya Garini (Fidelity : Jurnal Teknik Elektro, 2024)
The accurate measurement of electrical energy transactions using kWh meters is crucial to prevent losses for both consumers and utilities. However, the growing prevalence of nonlinear loads can introduce harmonics into the power system, potentially affecting the accuracy of kWh meter readings. This study aimed to investigate the impact of harmonics on the measurement accuracy of analog and electromechanical kWh meters. The results demonstrate that as the percentage of Total Harmonic Distortion (%THD) increases, due to the increased use of nonlinear loads, the measurement accuracy of both types of kWh meters decreases, potentially leading to financial losses for both consumers and the utility company. Based on the study, Simulation results demonstrate this impact, with analog and electromechanical kWh meters showing significantly different billing outcomes under resistive and capacitive loads. For example, a purely resistive 300-watt load resulted in a bill of Rp. 327,870 for the analog meter and Rp. 319,343 for the electromechanical meter. In contrast, a 300-watt capacitive load resulted in bills of Rp. 84,497 and Rp. 83,707, respectively.